(untitled) (Web of Teachers: Inderscience Research, 2026)
This study examines error correction techniques in English Language Teaching (ELT) and analyzes their pedagogical implications in classroom practice. It investigates how different corrective feedback strategies influence learners’ language development, accuracy, and communicative competence. The research focuses on major types of error correction, including explicit correction, recast, metalinguistic feedback, clarification requests, and elicitation, and evaluates their effectiveness in different instructional contexts. The study highlights that error correction is not merely a corrective act but an essential pedagogical tool that shapes learner awareness, interlanguage development, and language acquisition processes. Findings indicate that the effectiveness of error correction depends on multiple factors, including learner proficiency level, task type, instructional goals, and classroom interaction patterns. While explicit correction is effective for accuracy-focused learning, indirect techniques such as recasts and elicitation are more suitable for promoting fluency and learner autonomy.